2002
DOI: 10.1073/pnas.112218599
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific modulation of skeletal myogenesis by inhibitors of nuclear deacetylases

Abstract: Nuclear acetyltransferases promote and deacetylases inhibit skeletal muscle-gene expression, suggesting the potential effectiveness of deacetylase inhibitors (DIs) in modulating skeletal myogenesis. Surprisingly, previous studies have indicated that DIs suppress myogenesis. The recent observations that histone deacetylases associate with the muscle-regulatory proteins MyoD and MEF2C only in undifferentiated myoblasts prompted us to evaluate the effect of DIs at distinct stages of the myogenic program. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
103
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 24 publications
15
103
1
2
Order By: Relevance
“…In contrast, it has been reported that TSA inhibits the differentiation of adipocytes (22) or oligodendrocytes (23). In the skeletal muscle cell lineage, TSA either augments or inhibits the differentiation depending on the developmental stage (24). These findings suggest that TSA has differential effects in distinct cell types or developmental stages.…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast, it has been reported that TSA inhibits the differentiation of adipocytes (22) or oligodendrocytes (23). In the skeletal muscle cell lineage, TSA either augments or inhibits the differentiation depending on the developmental stage (24). These findings suggest that TSA has differential effects in distinct cell types or developmental stages.…”
Section: Discussioncontrasting
confidence: 50%
“…Concentrations ranging from 80 to 200 nmol/L promoted the formation of myosin-heavy chain (MyHC)-positive multinucleated myotubes with a size larger than those formed by controltreated myoblasts-an effect that was equivalent to that observed with previously tested HDACi, such as TSA (Figure 1) (14). The potential availability of givinostat in clinical practice, and the known pharmacological profile of givinostat in pediatric patients (15), prompted an interest in testing givinostat in preclinical studies for the treatment of DMD.…”
Section: Resultsmentioning
confidence: 64%
“…21 For TSA, we used the general concentration of 50 nM in accordance with previous reports, to serve as a positive control. 22,23 Almost all of the satellite cells were not viable after treatment at day 2 (data not shown); therefore, we selected day 3 (the myoblast stage) to start the treatment. To examine the cytotoxic effects of SFN, TSA and 5-aza-dC treatments on porcine satellite cell growth, we determined cell viability (Fig.…”
Section: Resultsmentioning
confidence: 99%